Experimental Study on Impact Failure Characteristics of Large-size Boulder Specimen by SHPB. Issue 2 (March 2021) - Cheng, Jinguo; Jiang, Hua; Jiao, Xingfei; Jiang, Yusheng; Zhu, Jiachen
Abstract: The issue of rock breaking is inevitable when shield excavating the strata rich in boulders with large size. Based on the one-dimensional elastic stress wave theory, the dynamic stress-strain relationship of rock specimens under single impact and cyclic impact load is obtained by using split Hopkinson pressure bar test system, and the variation law of absorbed energy with the changes of impact pressure or impact frequency is analyzed. The experiment results indicate that under single impact, when the impact pressure is added, the peak value of strain and stress increase; the dynamic elastic modulus of the specimen increases in the elastic stage, while increases at first and then decreases in the non-linear elastic loading stage. Also, the optimal impact energy exists corresponding to the maximum absorbed energy. Under the cyclic impact, the rock failure needs to meet the requirement of lowest impact energy. With the increase of impact pressure, the peak strain and single absorbed energy decrease at first and then increase, and the cumulative absorbed energy increases gradually. When the impact energy exceeds the energy required for rock failure, the rock is subject to primary impact failure. The research results can provide reference for the design of rock breaking cutters and the control of shield tunnelling parameters.